Prevention of Diabetes in Overweight/Obese Adults through Traditional Chinese Patent Medicine: Study Protocol for a Prospective Cohort Study - Bing Pang (Hindawi Limited, 2021)
Background. Early intervention in prediabetes can prevent or delay the incidence of type 2 diabetes mellitus (T2DM). Traditional Chinese patent medicine (TCPM) is widely used in China to prevent T2DM. This study aims to evaluate the efficacy and safety of TCPMs for preventing T2DM. Method/Design. This study is a multicenter, cohort study with two arms. A total of 600 participants will be recruited. The participants will be divided into either intervention or control groups according to their own desire, and the exposure factor is the application of TCPMs. All participants will be encouraged to lead a healthy lifestyle, and the intervention group also used TCPMs based on syndrome differentiation. Incident diabetes and normalization of blood glucose are indexes of end point. Safety assessments and adverse event monitoring will also be conducted. The treatment duration is set for 24 weeks, and we will follow-up for another 2 years. Discussion. This trial may provide initial evidence regarding the efficacy and safety of TCPMs plus lifestyle intervention (LI) compared to LI alone for preventing T2DM and provide a comprehensive intervention plans that choose suitable TCPMs for diabetes prevention according to syndrome differentiation. Trial Registration Number. Chinese Clinical Trial Registry ID: ChiCTR1900023541, registered on 1 Jun 2019. The version identifier is 2018121702.